Academic Senate Minutes 2016-02-04 - Academic Senate:::::::::
Chair Report. Agenda – Approved. Minutes of 12/17/15 – Approved. Consent Items: POLS major revision, Revision to Art – Photography concentration – Approved. Provost Report. Proposal for New Standing Committee – Academic Planning, Assessment and Resources approved. Vice Chair Report. Vice President of Administration and Finance Report. Vice President of Student Affairs Report. Associated Students Report. Statewide Senators Report. Revision to the Reappointment, Tenure and Promotion policy – First Reading. EPC Report. FSAC Report. SAC Report. CFA Report. Staff Report. Good of the Order.